Exploring the impact of pyrolysis temperature on nutrient composition of Gliricidia sepium biochar: a comprehensive study - Nuwarapaksha, T. D.; Dissanayaka, D. M. N. S.; Udumann, S. S.; Vinujan, Shanmugalingam; Atapattu, Anjana J. (Technology in agronomy, 2024)
Biochar is a carbon-rich, highly porous substance produced through pyrolysis at different temperatures using various feedstocks. The performance of biochar can vary based on the properties of the raw materials and the production process. The objective of this study was to evaluate the nutritional and structural properties of Gliricidia sepium biochar at different pyrolysis temperatures. Gliricidia sepium biochar was generated at temperatures ranging from 325 to 700 °C under a limited oxygen supply, with a heating rate set at 7 °C per minute, and a pyrolysis duration of 3 h. Nutritional and structural properties of the produced biochar were examined using a scanning electron microscope (SEM) combined with energy dispersive X-ray spectroscopy (EDX) technique. Results demonstrated a significant influence of pyrolysis temperature, particularly at lower heating rates, on the nutritional properties and structure of Gliricidia sepium biochar. A maximum biochar yield of 38.17% was achieved at 325 °C, underscoring the preference for lower pyrolysis temperatures in biochar production, while the minimum biochar yield of 27.43% was observed at 700 °C. Different biochar treatments exhibited significant differences (p < 0.05) in the yields of Carbon (C), Oxygen (O), Phosphorus (P), Calcium (Ca), Magnesium (Mg), Sulphur (S), and Sodium (Na). Conclusively, the production of biochar from Gliricidia sepium yielded a nutrient-rich resource that holds great potential as a soil amendment and future studies should need to explore the effects of pyrolysis duration, nutrient transfer capacity, and heavy metal composition of Gliricidia sepium biochar to further expand our understanding of its characteristics and applications.